(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Paulo Coelho is a Brazilian writer. He is well known for using rich symbolism in many of his works Brazilian author not only writes about self fulfilment and personal happiness, he also embodies his success stories. Coelho’s territorial independence made him the most famous Brazilian author abroad. His books have been translated into 81 languages and published in 170 countries. In the Novel, The Alchemist, even alchemy, the central symbol of the book, entails coaxing metal to achieve into own personal legend to turn into gold. As a result, the idea that all individuals should live in the singular pursuit of their individual dreams emerges as the primary theme of The Alchemist. The Alchemist, which has sold at least 65 millions of copies and holds a position in Guinness World Record for being one of the most widely translated books in the contemporary world. His mesmerizing novel “The Alchemist”, is regarded as one of the magnum opuses that deal with the self-recognition of the protagonist of the novel.